2003
DOI: 10.2355/isijinternational.43.1664
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Specific Energy Use in an Integrated Steel Plant-The Effect of an Optimisation Model

Abstract: Analysing the potential for improving the specific energy use in a steel mill can be difficult due to the interactions between the different subsystems. Changes in one unit can lead to several changes throughout the system. A process integration model taking into account the different interactions within the system is presented. The model is based on an optimising routine, making it a total analysis method for the steel plant system including the surroundings. The model is used to analyse the different possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 3 publications
0
47
0
1
Order By: Relevance
“…It was also shown that mixed-integer linear programming (MILP) provides a methodology for determining optimal strategies in order to minimise the overall energy costs in such industries [16]. Studies using such a methodology in a Swedish context include for example [17][18][19][20][21][22][23][24], where MIND (Method for analysis of INDustrial energy systems) was used. MIND is a method developed for optimization of dynamic industrial energy systems [17].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that mixed-integer linear programming (MILP) provides a methodology for determining optimal strategies in order to minimise the overall energy costs in such industries [16]. Studies using such a methodology in a Swedish context include for example [17][18][19][20][21][22][23][24], where MIND (Method for analysis of INDustrial energy systems) was used. MIND is a method developed for optimization of dynamic industrial energy systems [17].…”
Section: Introductionmentioning
confidence: 99%
“…The model used in this work is based on an existing model that was initially developed for analysis of the energy use for an integrated steel plant, and the model has been validated by using actual production data [13]. This model has been successfully used in several studies mainly focusing on material, energy use and production cost C. WANG ET AL.…”
Section: Validationmentioning
confidence: 99%
“…The reMIND tool has been used in several industries, such as the Swedish foundry industry [2], steel industry [4,[35][36] and pulp and paper mills [6,39] as well as district heating systems [7]. In these studies the ESO tool reMIND is used to find the optimal operation strategy and investigate how different boundary conditions, such as changes in electricity and fuel prices, influence the system.…”
Section: Energy Systems Optimisation (Eso) Toolmentioning
confidence: 99%